Refugee-focused service providers: improving the welcome in New Zealand. Issue 9 (27th July 2019) - McIntosh, Alison; Cockburn-Wootten, Cheryl
ABSTRACT: When refugees are resettled into a destination, refugee-focused service providers offer frontline services to ease refugees' experiences of trauma and marginalisation, providing advocacy and welcome through reception processes, translation services and multicultural centres. The degree and effectiveness of welcome given by these service providers are of importance to how quickly refugees feel they belong and can settle in their new society. This paper presents the findings of original research conducted with 34 refugee-focused service providers in New Zealand. Ketso, a creative, participatory tool was used as a community engagement method. The results indicate how these service providers felt the welcome, advocacy and support for refugees could be better organised to support the resettlement process. The barriers and challenges to the provision of welcome are discussed, and priorities identified to improve the refugee resettlement process and outcomes.